Identification of New Genes Related to Virulence of Xanthomonas axonopodis Pv. Citri during Citrus Host Interactions - Ferreira, Cristiano B. [UNESP]; Moreira, Leandro M.; Brigati, Joice B.; Lima, Lonjore L. [UNESP]; Ferro, Jesus A. [UNESP]; Ferro, Maria I. T. [UNESP]; Oliveira, Julio C. F. de (Hans Publishers, 2017)
A mutant library of the bacterium Xanthomonas citri subsp. citri strain 306 pathotype A (Xac), the causative agent of most aggressive Asiatic type A citrus canker, was screened regarding altered canker symptoms after inoculations into Citrus sinensis and Citrus limonia host leaves. Twenty-six mutants have shown phenotypic virulence changes and have respectively knocked out gene identified by sequencing. In vivo growth curves were obtained for nine mutants to quantify how the mutations could affect pathogen's adaptability to growth inside and attack host plant infected tissue. Among identified genes in mutated strains, we could find those that until now had not been reported as being involved in Xac adaptation and/or virulence, such as predicted to encode for xylose repressor-like protein (XAC Delta xylR), Fe-S oxidoredutase (XAC Delta aslB), helicase IV (XAC Delta helD), ubiquinol cytochrome c oxidoreductase iron-sulfur subunit (XAC Delta petA), chromosome partitioning protein (XAC Delta parB) and cell division protein FtsB (XAC Delta ftsB), in addition to genes predicted to encode for hypothetical proteins. The new genes found in this study as being relevant to adaptation and virulence, improve the understanding of Xac fitness during citrus plant attack and canker symptoms development.
Keywords: Xanthomonas axonopodis Pv. Citri; Mutants; Impaired Virulence